The Association Between Usage of Colchicine and Pneumonia: A Nationwide, Population-Based Cohort Study - Tsai, Tsung-Lin; Wei, James Cheng-Chung; Wu, Yue-Ting; Ku, Yueh-Han; Lu, Kun-Lin; Wang, Yu-Hsun; Chiou, Jeng-Yuan (Frontiers in Pharmacology, 2019)
Objectives A previous study suggested that colchicine may cause leukopenia, and increase the risk of infection, such as pneumonia. Thus, we investigated the potential relationship between colchicine use and risk of developing pneumonia. Methods Data were collected from Taiwan’s National Health Insurance Research Database, a nationwide, population-based database. A 13-year retrospective cohort study was conducted, and all investigated subjects were identified by International Classification of Disease, Ninth Revision, Clinical Modification, codes between 2000 and 2012. Propensity score matching was applied to adjust for potential confounding variables, and then Cox proportional hazard model was used to evaluate the hazard ratio (HR) of pneumonia in gout and its associations with colchicine use, colchicine dosage, and days of colchicine use. Results 24,410 gout patients were enrolled, including 12,205 cases treated with colchicine (colchicine group) and 12,205 cases not receiving colchicine (non-colchicine group). The overall incidence rates of pneumonia in colchicine group and non-colchicine group were 18.6 and 12.6 per 1000 person-years, respectively. The colchicine group had a higher risk of pneumonia as compared with non-colchicine group (adjusted HR=1.42, 95% CI 1.32 to 1.53, P<0.05). High cumulative dose and days of colchicine use notably increased the risk of contracting pneumonia. Conclusion This nationwide population-based cohort study reveals that gout patients taking colchicine are at increased risk of developing pneumonia compared with gout patients who don’t use colchicine. Therefore, it’s crucial that gout patients being treated with colchicine be given the minimally effective dosage for the shortest possible duration to minimize their risk of pneumonia.